Sistema de monitoramento de rede com software livre - Arakaki, Rafael Tartari (2011)
This project aims to present the application, configuration, logic development and results obtained when applying network management, by taking as initial premise the choice of open source platform, ie, with no cost, as a alternative way of implantation. Open source systems are often related to bad interfaces or synonym of low quality, these comparisons misleading, because, once there is the correct programming and implementation, it allows you to reduce a lot the costs (or even become zero) beyond to execute the same functions of a paid application, when you want to manage the network.